2012 19th International Conference on Telecommunications (ICT) 2012
DOI: 10.1109/ictel.2012.6221311
|View full text |Cite
|
Sign up to set email alerts
|

Statistical decision making method for cognitive radio

Abstract: This work is about developing a decision making method, based on statistical modeling, for a cognitive radio receiver. By characterizing statistically the radio metrics, the intelligent equipment will be capable of making decisions on actions of reconfigurations, in order to adapt to the state of the environment. Through the adaptability of the radio receiver to the environment, we try also to reduce energy consumption by treating one scenario of reconfigurability which consists of switching off the equalizer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Since the environment is described statistically the errors of the radio sensors are taken into account in the decision making and this reduces the probabilities of false alarm and false decision with a reduced computational complexity. We have justified this result in another work [13] where we applied the cognitive engine designed in this paper to the scenario of adapting the use of the equalizer in the receiver chain according to the level of the inter-symbol interferences. In our future work, we will use our cognitive engine to treat other scenarios of adapting the radio receiver.…”
Section: Discussionmentioning
confidence: 71%
“…Since the environment is described statistically the errors of the radio sensors are taken into account in the decision making and this reduces the probabilities of false alarm and false decision with a reduced computational complexity. We have justified this result in another work [13] where we applied the cognitive engine designed in this paper to the scenario of adapting the use of the equalizer in the receiver chain according to the level of the inter-symbol interferences. In our future work, we will use our cognitive engine to treat other scenarios of adapting the radio receiver.…”
Section: Discussionmentioning
confidence: 71%
“…For a multipath channel from length L , ( h 0 ,..., h L − 1 ), disturbed by an added Gaussian noise, we have defined, in previous works [ Bourbia et al , , ], two metrics required for the evaluation of the environment and for the decision making. These metrics are SNR p and ISI which represent respectively the signal‐to‐noise ratio, measured for the path that has the highest energy, and the power of the intersymbol interference.…”
Section: Decision‐making Methods By Statistical Modeling Of the Radio mentioning
confidence: 99%
“…The estimation of the two metrics is based on the channel estimation. In Bourbia et al [] we have made a study on different algorithms of channel estimation proposed in the literature. After this study we concluded that the LMS (Least Square Error) algorithm is the most appropriate in our case for the estimation of SNR p and ISI since it provides the best compromise between the minimum estimation error and the minimum computational complexity.…”
Section: Decision‐making Methods By Statistical Modeling Of the Radio mentioning
confidence: 99%
“…In this section, we will describe the method that we have developed in order to determine the decision rule to make decision for using or not using the equalizer from the statistical modeling of the environment [15].…”
Section: Statistical Modeling Of the Environment And Decisionmentioning
confidence: 99%